Transformasi Digital : Dampak, Tantangan, Dan Peluang Untuk Pertumbuhan Ekonomi Digital - Dian Sudiantini; Mayang Puspita Ayu; Muhammad Cheirnel All Shawirdra Aswan; Meyliana Alifah Prastuti; Melani Apriliya (Universitas 45 Surabaya, 2023)
There are many challenges in dealing with digital economic transformation, such as unclear regulations, taxation issues, unfair competition, and uneven digitalisation. If these challenges are viewed from education and skills, they can be broken down into skills gaps, changes in workforce requirements, and low digital literacy. Of course these things happen because of a lack of technological infrastructure, limited internet access and low quality of internet access, but other than that this is all an ongoing process. Digital economy transformation is a process that must require support from all internal sectors in Indonesia to invest in information and communication technology. Businesses and governments around the world are actively developing strategies to harness the transformational potential of the digital economy to enhance economic growth and create new opportunities for people and businesses. Therefore this writing is aimed at explaining the development, transformation, trends and innovations as well as their good and bad impacts. In the end, many opportunities will be felt by business people in this digital era, especially for global partnerships in developing their business to be more effective and efficient.